Description, measurement and evaluation of tertiary-education food environments. Issue 9 (7th March 2016) - Roy, R.; Hebden, L.; Kelly, B.; De Gois, T.; Ferrone, E. M.; Samrout, M.; Vermont, S.; Allman-Farinelli, M.
Abstract: Obesity in young adults is an increasing health problem in Australia and many other countries. Evidence-based information is needed to guide interventions that reduce the obesity-promoting elements in tertiary-education environments. In a food environmental audit survey, 252 outlets were audited across seven institutions: three universities and four technical and further education institutions campuses. A scoring instrument called the food environment-quality index was developed and used to assess all food outlets on these campuses. Information was collated on the availability, accessibility and promotion of foods and beverages and a composite score (maximum score=148; higher score indicates healthier outlets) was calculated. Each outlet and the overall campus were ranked into tertiles based on their 'healthiness'. Differences in median scores for each outcome measure were compared between institutions and outlet types using one-way ANOVA with post hoc Scheffe's testing, χ 2 tests, Kruskal–Wallis H test and the Mann–Whitney U test. Binomial logistic regressions were used to compare the proportion of healthy v . unhealthy food categories across different types of outlets. Overall, the most frequently available items were sugar-sweetened beverages (20 % of all food/drink items) followed by chocolates (12 %), high-energy (>600 kJ/serve) foods (10 %), chips (10 %) and confectionery (10 %). Healthy food and beverages were observed to be less available, accessible and promoted than unhealthy options. The median score across all outlets was 72 (interquartile range=7). Tertiary-education food environments are dominated by high-energy, nutrient-poor foods and beverages. Interventions to decrease availability, accessibility and promotion of unhealthy foods are needed.